Kelayakan media komik interaktif mata pelajaran IPA pada siswa kelas V sekolah dasar di Kecamatan Mlonggo Jepara - Rani Susanti (IKIP Siliwangi, 2023)
This study aims to analyze the feasibility of interactive comic media for science subjects in fifth grade elementary school. This research belongs to the type of Research and Development (R&D) research with research and development procedures consisting of two stages, namely media development and media testing. The method used for the development and testing of learning media uses the Borg and Gall model. The product trial design used a pretest posttest control group design on students at SDN 2 Jambu as the experimental class and students at SDN 11 Jambu as the control class. Data were collected by observation, questionnaires, tests, interviews and documentation. The data from the validation results were analyzed by accumulating the number of scores. The interactive comic was developed based on a needs analysis conducted on fifth grade students and teachers in three elementary schools in Mlonggo sub-district, Jepara district. The product developed is in the form of interactive comics for science subjects. The interactive comics proved to be feasible because the total scores obtained from the four validators were 88 and 86, respectively, with the â€œvery decentâ€ score criteria. The results of the responses from students were 88.50% and the responses from teachers in three elementary schools with an average of 87.80% with the product category